Sistem Keamanan Sepeda Motor Menggunakan Atmega16 dengan Short Message Service (SMS) Gateway - Dedi Sulistyo; Cicilia Puji Rahayu (Politeknosains, 2018)
The increased crime of motorcycle theft and plunder in the State of Indonesia makes citizens increasingly feel insecure. Although various ways are done to prevent theft and seizure of motorcycles, among others, by replacing the ignition key model or installing a double key still does not make thieves desperate. Making this tool is intended to reduce the theft and seizure of motorcycles. With this tool will make it easier for the owners of motorcycles because the system works this tool by utilizing sms facilities. The working principle of this tool when the vehicle contact ON, motorcycle users are required to enter a password of 4 digit number. If the password is correct, the machine can be turned on, but if the password is entered incorrectly, the machine can not be turned on, the horn will sound on a regular basis, and the modem will send an alert SMS to the owner of the motorcycle. This tool can work effectively because it can reduce the theft of a motorcycle, this tool can also be used as an alternative safeguard on other motor vehicles.